Seeds for needs: adaptation to climate change - Innovative tools to match seeds to the needs of women farmers in Ethiopia - Gevel, Jeske M.J, van de; Gellaw A; Fadda, Carlo (Bioversity International, 2013)
As climate change continues to drastically affect food security around the world, many farmers are in need of new crops and crop varieties that can be grown in the changed environment of their farms. Adaptation options to climate change already exist in genebanks and other farmers’ fields in the form of germplasm and seeds, but the challenge is to identify them and then disseminate them in the right environments and under the right conditions, and in ways that satisfy the needs of farmers and increase the resilience of the productive systems. There is a general consensus among farmers interviewed in household survey and focus group discussion that there is an increased temperature and decreased rainfall; in addition, rainfall is also perceived to be more erratic and the rainy season shorter, thus there is a decline in the length of growing period. This is affecting the productivity of two major cereals in smallholder farmers’ production system: barley and durum wheat. One possible answer to this is to provide farmers with varieties that are better adapted to the existing climatic conditions. Ethiopia is endowed with a large amount of the needed diversity conserved in the national gene bank at the Institute of Biodiversity Conservation (IBC).